2019
DOI: 10.3390/molecules24050828
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Infant Faecal Fermentation of Low Viscosity Barley β-Glucan and Its Acid Hydrolyzed Derivatives: Evaluation of Their Potential as Novel Prebiotics

Abstract: Barley contains high level of β-1,3-1,4-glucans (BBGs) which can be fermented by microbes and are a potential prebiotic. In the present study, native BBG with low viscosity and a MW of 319 kDa was depolymerized by acid hydrolysis to produce a series of four structurally characterized fragments with MWs ranging from 6–104 kDa. In vitro fermentation of these BBG samples by infant faecal microbiome was evaluated using a validated deep-well plate protocol as parallel miniature bioreactors. Microbial taxa were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
3
12
0
Order By: Relevance
“…In contrast to native oat β-glucan that was not fermented by infant fecal microbiota, endo-1,3(4)-β-glucanase-treated oat β-glucan was degraded by the fecal microbiota of both 2- and 8-week old infants. This result corroborates the findings of Lam et al [ 19 ], who observed an increase in SCFA production when lowering the molecular weight of barley β-glucans in an in vitro fermentation study using infant fecal inocula. We also found that decreasing the size of oat β-glucans by enzyme treatment resulted in a stronger stimulation of Enterococcus and increased production of lactic acid, which were more pronounced in the fecal inoculum of 2-week-old infants.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast to native oat β-glucan that was not fermented by infant fecal microbiota, endo-1,3(4)-β-glucanase-treated oat β-glucan was degraded by the fecal microbiota of both 2- and 8-week old infants. This result corroborates the findings of Lam et al [ 19 ], who observed an increase in SCFA production when lowering the molecular weight of barley β-glucans in an in vitro fermentation study using infant fecal inocula. We also found that decreasing the size of oat β-glucans by enzyme treatment resulted in a stronger stimulation of Enterococcus and increased production of lactic acid, which were more pronounced in the fecal inoculum of 2-week-old infants.…”
Section: Discussionsupporting
confidence: 92%
“…As enterococci are known to be among the first colonizers of the infant gut [ 43 ], the increase in enterococci might be relevant in infants for creating a new environment that allows colonization of the gut by strict anaerobes [ 2 , 20 ]. A similar stimulation of Enterococcus was shown in an in vitro fermentation study of barley β-glucans using the fecal microbiota of 9–15-month old infants which received both human milk and solid foods [ 19 ]. With these age groups, substantial production of SCFAs was also observed, which indicates that the fecal microbiota of 9–15-month-old infants are capable of degrading native oat β-glucan.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Yogurt added with 3% POAE had the highest total acid content (P<0.05). POAE could be utilized by LAB as additional carbon source as POAE contains β-glucan, a water-soluble dietary fiber and a prebiotic (Sari et al, 2017;Lam et al, 2019). This could increase the production of acid by LAB, thus the total acid content of yogurt added with 3% POAE was higher than the others.…”
Section: Physical Propertiesmentioning
confidence: 99%